Pengaruh Relationship Marketing dan Keberagaman Produk Terhadap Loyalitas Konsumen Pada Toko PM Collection Pekanbaru - Siti Purnama; Meyzi Heriyanto; Syofiatul Safitri (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
This study aims to determine and analize the application of relationship marketing and product diversity on consumer loyalty at PM Collection Pekanbaru.The method used this stud describtive quantitative ith SPSS version 23 program. The population in his stdy ere all consumers ho made purchases at PM Collection who found 10.800 people and the sample of this study as 99 respondents from PM Collection Pekanbaru consumers. The sampling technique through used in this study is accidental sampling. For data collection techniques through questionnaires and the used of a Likert scale, the types and sources of data used primary and secondary data. The data analysis includes validity test, reliability test, classical assumption test of normality,calassic multicollinearity assumption test, classical assumption test of heteroscedasticity, and murtiple linear analisis along with analylisis of the coefficient of deremination (R2), sugnificant test ith with partial test ( T test ), simultaneous test ( F test ). In this study the obtaines are that relationship marketing (X1) has a possitive and significant effect on consumer loyalty (Y), diversity product (X2) has a positive and significant on consumer loyalty (Y) and relationship marketing (X1) and diversity product (X2) has a possitive and significant effect on consumer loyalty (Y). Thus, PM Collection Pekanbaru has paid attention to all the factors that make consumers come back and add more complete product brands and sizes, so that consumers are interested in coming and buying at the PM Collection Pekanbaru.